Clinical management of pulmonary disorders and diseases - Pokorski, Mieczyslaw (Advances in experimental medicine and biology. Neuroscience and respiration, 2017)
The book endeavors to provide a stimulating and thought provoking scientific content to share and exchange new clinical studies and advancements in dealing with pulmonary diseases. The topics vary from clinical to translational research in respiratory diseases such as lung cancer, obstructive sleep apnea, chronic obstructive pulmonary disease, bacterial and fungal infections, lung lesions during febrile maladies, and others. An attempt has been made to show the intertwined relationship between the pulmonary system and other body systems such as kidney, cardiac, or hormonal functions. The ensuing interlocked morbidities, often exacerbating one another, require the coordination of various medical specialties to optimize the diagnostic and therapeutic processes. The knowledge sharing through publications of research and clinical experiences is indispensable to accelerate the innovation spectrum and to continue working on the therapeutic and preventive strategies in chronic pulmonary diseases. The book is addressed to pulmonologists, chest physicians, researchers, and healthcare professionals engaged in patient care.